THE SIMPLICITY OF SELF-KNOWLEDGE AFTER AVICENNA. Issue 2 (10th August 2018) - Adamson, Peter
Abstract: Alongside his much-discussed theory that humans are permanently, if only tacitly, self-aware, Avicenna proposed that in actively conscious self-knowers the subject and object of thought are identical. He applies to both humans and God the slogan that the self-knower is "intellect, intellecting, and object of intellection ( 'aql, 'āqil, ma'qūl )". This paper examines reactions to this idea in the Islamic East from the 12th-13th centuries. A wide range of philosophers such as Abū l-Barakāt al-Baghdādī, Faḫr al-Dīn al-Rāzī, al-Šahrastānī, Šaraf al-Dīn al-Mas'ūdī, al-Abharī, al-Āmidī, and Naṣīr al-Dīn al-Ṭūsī raised and countered objections to Avicenna's position. One central problem was that on widely accepted definitions of knowledge – according to which knowledge is representational or consists in a relation – it seems impossible for the subject and object of knowledge to be the same. Responses to this difficulty included the idea that a self-knower is "present" to itself, or that here subject and object are different only in "aspect ( i'tibār )". Résumé: Au cours de son exposé de sa thèse si disputée selon laquelle les êtres humains sont de manière permanente, fût-ce tacitement, conscients d'eux-mêmes, Avicenne suggère que dans les auto-connaissants activement conscients, le sujet et l'objet de la pensée sont identiques. Il applique alors – à la fois aux êtres humains et à Dieu – le slogan affirmant que l'auto-connaissant est « intellect, intelligeant et intelligé » ( 'aql, 'āqil, ma'qūl ). Cet article examine les réactions à cette idée dans l'Est du monde islamique durant les 12ème et 13ème siècles. Un grand nombre de philosophes, tels Abū l-Barakāt al-Baghdādī, Faḫr al-Dīn al-Rāzī, al-Šahrastānī, Šaraf al-Dīn al-Mas'ūdī, al-Abharī, al-Āmidī et Naṣīr al-Dīn al-Ṭūsī ont en effet soulevé des objections à l'encontre de la position d'Avicenne et ont apporté des réponses à ces objections. Un problème central a consisté dans le fait que selon des définitions généralement acceptées de la connaissance – d'après lesquelles la connaissance est représentationnelle ou consiste dans une relation –, il paraissait impossible pour le sujet et l'objet de la connaissance d'être le même. Des réponses à cette difficulté ont mis en place l'idée que tout autoconnaissant est « présent » à soi, ou que dans ce cas, le sujet et l'objet sont différents seulement selon l' « aspect » ( i'tibār ).